Pelatihan Ecoprint: Kerajinan Ramah Lingkungan di Desa Batuliman Indah. Candipuro, Lampung Selatan - Dermawan, Oki; Rahmadhani, Salsabila Shafa; Sari, Cindi Lupita; Luthfiyatunnisa, Luthfiyatunnisa; Sari, Dessy Rusmia (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service aimed to raise environmental awareness and provide education to the residents of Batuliman Indah Village, Lampung Selatan Regency, through a training workshop on the ecoprint technique, an environmentally friendly method of printing natural motifs using natural dyes. The activity began with the preparation of materials, followed by an introduction to the theory and hands-on practice of ecoprinting techniques, which involved selecting leaves and flowers and applying them to fabric. The results of this activity indicated that participants successfully mastered the ecoprinting technique, producing a variety of aesthetically pleasing craft products with diverse motifs. The community exhibited high enthusiasm, developing additional products such as bags and cushion covers, and increased awareness about the use of natural materials in production. With these new skills, it is hoped that the community will adopt ecoprinting as a sustainable craft that positively impacts both the environment and the local economy